Organizacja prefektury annony w okresie pryncypatu - Wojciech Wierzbicki (Studia Antiquitatis et Medii Aevi Incohantis)
(The organisation of the prefecture of annona during the principate): Standing at the head of the grain administration, the equestrian prefect (praefectus annonae) was responsible during the early Empire for the process of supplying the capital with grain – the main staple of the Eternal City’s inhabitants’ diet. The article outlines the organisational background to the whole project, as well as the personal involvements of various emperors because of the political importance of the process of supplying Rome with grain.